Interest Rate Variations, Mortgage Prepayments and Household Mobility - Quigley, John M. (The Review of Economics and Statistics, 1987)
The volatility of interest rates and the deregulation of the mortgage lending sector have meant that many homeowners also own mortgages at terms more favorable than current interest rates. This paper presents a model of residential mobility decisions and an empirical analysis that evaluates the importance of the ownership of these mortgages upon the mobility of homeowners. The results, based upon proportional and nonproportional hazard models, indicate that these effects are quite large. The empirical analysis distinguishes between different regulatory regimes that govern the assumption of existing mortgages, and indicates the implications of these findings for the pricing and valuation of mortgage-backed securities. Copyright 1987 by MIT Press.